Sverdlovchanin: a new apple cultivar for the Middle Urals - D. D. Telezhinskiy; L. A. Kotov; S. A. Makarenko; G. N. Tarasova (Труды по прикладной ботанике, генетике и селекции)
The Middle Urals is a region of risky agriculture. Apple cultivars of more southern origin are usually unpromising due to insufficient level of hardiness, so there is a need to develop and deploy local apple-tree cultivars. The staff of Sverdlovsk Horticultural Breeding Station released a new apple cultivar, ‘Sverdlovchanin’. This cultivar is notable for high winter hardiness, productivity (average yield is ca. 18.0 t/ha), and low fruit shedding rate at harvest maturity. Its fruits are beautiful, uniform, yellow, roundish, weighing 110 g (maximum 205 g), with a very good sweet and sour dessert flavor. The ripening time under the conditions of the Middle Urals is usually late September, and fruits can be stored until the end of February. The author of this cultivar is L. A. Kotov The apple cultivar ‘Sverdlovchanin’ was included in the State Register of Breeding Achievements of the Russian Federation in 2018.